Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014 IEEE International Frequency Control Symposium (FCS) 2014
DOI: 10.1109/fcs.2014.6859991
|View full text |Cite
|
Sign up to set email alerts
|

All Digital Frequency Synthesis based on Pulse Direct Digital Synthesizer with spurs free output and improved noise floor

Abstract: This work presents Direct-Digital Frequency Synthesis architectures based on the classical Pulse-Direct Digital Synthesizer and using two quantization paths with opposite dithers or multi-path quantization with independent dithers to achieve spurs-free output with improved dynamic range. The proposed architectures are studied mathematically and the theory is supported by MATLAB simulation results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In this case it can be shown [13][14] 3.01 DR f s = − dB [13]. Note that the dynamic range observed in Fig.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this case it can be shown [13][14] 3.01 DR f s = − dB [13]. Note that the dynamic range observed in Fig.…”
Section: Introductionmentioning
confidence: 78%
“…Here M dithering and quantization paths following the LUT, with mutually independent, IID and uniformly distributed in [ ] ( ) 10 10 log M dB compared to that of Fig. 3, [13].…”
Section: Enhancing the Dynamic Rangementioning
confidence: 99%
“…The problem of generating spurious-free output with a dithered PDDS has been studied in abstract form in [9]. It is shown that random dithering having appropriate statistics results in spurs-free output [9]- [11]. However, in some sense, dithering converts the frequency spurs into a noise floor.…”
Section: Forward Architecturesmentioning
confidence: 99%
“…5 [11]. The output is spurs-free and the DR, defined as the ratio of the power of the desirable signal to the power spectral density (PSD) of the near-in noise s e is DR = 10 log 10 (f s ) − 3.01 dB, (in the continuous time-domain) [10], [11].…”
Section: A Eliminating Spurs With Ditheringmentioning
confidence: 99%
“…use of colored random sequences, (without feedback) can improve the dynamic range but not a lot [4][5].…”
Section: Introductionmentioning
confidence: 99%